Measuring legitimacy: new trends, old shortcomings? - Christian von Haldenwang (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The legitimacy of political orders is an important reference point in political analysis, but the concept is difficult to operationalise and measure – particularly in those countries where legitimacy is critical (cases of political transformation and high state fragility). This paper develops a four-fold analytical framework based on a dialogical understanding of legitimacy. To be successful, legitimation (the strategic procurement of legitimacy) has to fulfill two separate functions: it has to relate demands for legitimation to government performance, and relate the legitimacy claims issued by the rulers to behavioural patterns of individual and collective actors. The paper gives an overview of recent attempts to measure legitimacy. It argues that these attempts largely fail to conceptualise legitimacy in a convincing way. As a result, extant approaches measure only specific types of legitimacy – or they do not measure it at all.
Keywords: 330; Governance; Demokratie und Autokratie